Calcium-Sensing Receptor Is Functionally Expressed in the Cochlear Perilymphatic Compartment and Essential for Hearing - Minakata, Toshiya; Inagaki, Akira; Yamamura, Aya; Yamamura, Hisao; Sekiya, Shinji; Murakami, Shingo (Frontiers in Molecular Neuroscience, 2019)
Maintaining Ca2+ homeostasis in lymphatic fluids is necessary for proper hearing. Despite its significance, the mechanisms that maintain the cochlear lymphatic Ca2+ concentrations within a certain range are not fully clarified. We investigated the functional expression of calcium-sensing receptor (CaSR), which plays a pivotal role in sensing extracellular Ca2+ concentrations. Western blotting for CaSR revealed an approximately 130-kDa protein expression in cochlear tissue extracts and immunohistochemical analysis revealed its expression specifically in type I fibrocytes in the spiral ligament, fibrocytes in the supralimbal and limbal regions, the epithelium of the osseous spiral lamina, and the smooth muscle cells of the spiral modiolar arteries. Ca2+ imaging demonstrated that extracellular Ca2+ increased the levels of intracellular Ca2+ in CaSR-expressing fibrocytes in the spiral ligament, and that this was suppressed by the CaSR inhibitor, NPS2143. Furthermore, hearing thresholds were moderately elevated by intracochlear application of the CaSR inhibitors NPS2143 and calhex231, across a range of frequencies (8-32 kHz). These results demonstrate the functional expression of CaSR in the cochlear perilymphatic compartment. In addition, the elevated hearing thresholds that are achieved by inhibiting CaSR suggest this is a required mechanism for normal hearing, presumably by sensing perilymphatic Ca2+ to stabilize Ca2+ concentrations within a certain range. These results provide novel insight into the mechanisms regulating Ca2+ homeostasis in the cochlea and provide a new perspective on cochlear physiology.